Relations of combat stress and posttraumatic stress disorder to 24-h plasma and cerebrospinal fluid interleukin-6 levels and circadian rhythmicity. (February 2019) - Agorastos, Agorastos; Hauger, Richard L.; Barkauskas, Donald A.; Lerman, Imanuel R.; Moeller-Bertram, Tobias; Snijders, Clara; Haji, Uzair; Patel, Piyush M.; Geracioti, Thomas D.; Chrousos, George P.; Baker, Dewleen G.
Highlights: First cross-group, time-matched, sequential 24-h plasma and CSF IL-6 sampling study. No significant group differences in 24-h IL-6 levels in either CSF or plasma. Combat stress associated with blunted plasma but not CSF circadian IL-6 pattern. Evidence for a particular link between traumatic stress, immune and circadian system. Temporal immune asynchrony in stress-exposed individuals as developmental risk factor. Abstract: Background: Acute and chronic stress can lead to a dysregulation of the immune response. Growing evidence suggests peripheral immune dysregulation and low-grade systemic inflammation in posttraumatic stress disorder (PTSD), with numerous reports of elevated plasma interleukin-6 (IL-6) levels. However, only a few studies have assessed IL-6 levels in the cerebrospinal fluid (CSF). Most of those have used single time-point measurements, and thus cannot take circadian level variability and CSF-plasma IL-6 correlations into account. Methods: This study used time-matched, sequential 24-h plasma and CSF measurements to investigate the effects of combat stress and PTSD on physiologic levels and biorhythmicity of IL-6 in 35 male study volunteers, divided in 3 groups: (PTSD = 12, combat controls, CC = 12, and non-deployed healthy controls, HC = 11). Results: Our findings show no differences in diurnal mean concentrations of plasma and CSF IL-6 across the three comparison groups. However, a significantly blunted circadian rhythm of plasma IL-6 across 24 h was observed in all combat-zone deployed participants, with or without PTSD, in comparison to HC. CSF IL-6 rhythmicity was unaffected by combat deployment or PTSD. Conclusions: Although no significant group differences in mean IL-6 concentration in either CSF or plasma over a 24-h timeframe was observed, we provide first evidence for a disrupted peripheral IL-6 circadian rhythm as a sequel of combat deployment, with this disruption occurring in both PTSD and CC groups. The plasma IL-6 circadian blunting remains to be replicated and its cause elucidated in future research.